2010
DOI: 10.1021/ac1003085
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Arrays for Screening Cancer Specific Peptides

Abstract: In this paper, we describe a novel method to screen peptides for specific recognition by cancer cells. Seventy peptides were synthesized on a cellulose membrane in an array format, and a direct method to study the peptide-whole cell interaction was developed. The relative binding affinity of the cells for different peptides with respect to a lead 12-mer p160 peptide, identified by phage display, was evaluated using the CyQUANT fluorescence of the bound cells. Screening allowed identification of at least five n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 41 publications
3
92
0
Order By: Relevance
“…Incubation of the target with the peptide array and analysis of interactions between target and the spotted sequences can lead to identification of molecules with increasing binding affinity. In recent studies, peptide arrays were successfully applied for the identification of peptide-cell interactions [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Incubation of the target with the peptide array and analysis of interactions between target and the spotted sequences can lead to identification of molecules with increasing binding affinity. In recent studies, peptide arrays were successfully applied for the identification of peptide-cell interactions [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Peptide microarrays have been primarily used within screening settings with follow-up experiments focusing on a small number of promising candidates to ensure specificity [4]. Unidentified reactive peptides from a peptide microarray experiment cannot be distinguished from the large number of rightfully excluded unreactive peptides and are thus not further regarded.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesized peptides are spotted in a grid-layout on glass slides which allow the screening of thousands of peptides within a single experiment with requiring only a small quantity of sample. Applications range from studying the humoral response to HIV [1] or food allergens [2] to the detection of cancer biomarkers [3] and antibody signatures [4] to the characterization of protein-protein interactions [5] and of kinase substrates [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, no binding of the P1 and P2 was observed to human normal cells derived from different sources, including mammary epithelial cells (HMEC), peripheral blood mononuclear cells (PBMC), human umbilical vein endothelial cells (HUVEC), normal colon fibroblast, and human CD34+ bone marrow cells [19]. RGDPAYQGRFL peptide (P3) and WXEAAYQRFL peptide (P4) were identified by Kaur et al by a peptide arraywhole cell interaction approach [21]. Flow cytometry and confocal microscopy studies showed that the RGD-containing peptide was highly selective to MDA-MB-435 and MCF-7 cancer cells, but had very little affinity for the control HUVEC cells.…”
Section: Introductionmentioning
confidence: 99%